Use of the third person for self-reference by Jesus and Yahweh : a study of Illeism in the Bible and ancient Near Eastern texts and its implications for Christology /: a study of Illeism in the Bible and ancient Near Eastern texts and its implications for Christology. (2017) - Elledge, Roderick
No abstract available